Exploring Graduate Employability in Relation to their English Language Proficiency: A Preliminary Study - Kamsilawati Kamlun; Esther Jawing; Jualang Bin Abdullah Gansau (Penerbit Universiti Malaysia Sabah, 2020)
Recent literature has suggested that the relationship between globalisation and English language proficiency implicates employability in the job market. However, it could differ in different occupational groups as well as in different countries. Therefore, this study aims to investigate whether there is an effect on the graduate’s employability based on the student’s English language proficiency and their Malaysian University English Test (MUET) results. A total of 8,995 graduates who graduated in 2015 and 2016 were surveyed using data from the feedback method administered by the Ministry of Higher Education Malaysia from the Graduate Tracer Study 2015. The model used in this analysis would test the hypothesis as to whether there is a significant association between English language proficiency based on their MUET outcomes and their English language proficiency courses with the job status of UMS graduates in relation to their English language proficiency. In order to classify factors that influence graduate employability, an extensive analysis of the current literature is also used. For both local and global higher education contexts, the conceptual structure developed for this study applies. The knowledge offers insights into the growth of student employability and support needs for students to improve their graduate employability.